P15 Inequalities in alcohol-related mortality: an electronic cohort study of internal migration in wales. (2nd September 2017) - Gartner, A; Farewell, D; Greene, G; Trefan, L; Paranjothy, S; Fone, D
Abstract : Introduction: Alcohol-related deaths show a strong socioeconomic gradient. Selective migration, when individuals in poorer health move to more deprived areas, or vice versa, is associated with widening health inequality. However, it is not known whether recent internal migration contributes to the observed health inequality in alcohol-related deaths. This study aims to investigate whether selective migration of individuals is associated with the alcohol-related mortality gradient. Methods: We constructed a record-linked electronic cohort of the total population of Wales registered with a GP on 01/01/2006 (n=3 136881) with six-years' follow-up to 31/12/2011 in the SAIL Databank at Farr@Swansea. The Welsh Demographic dataset provided information on age, sex, and the lower super output area (LSOA) (n=1896) of residence at each of the 24 quarters, used to code migration. To each LSOA code we linked tenths of the Welsh Index of Multiple Deprivation 2008 and the ONS Rural-Urban definition. To code alcohol-related mortality (n=2224 of 184 247 deaths) using the standard ONS definition we linked the demographic dataset to the ONS mortality files. We estimated hazard ratios (HR) with 95% confidence intervals (95% CI) using Cox regression for the risk of alcohol-related death for deprivation fifths, adjusting for age-group, sex and rural-urban status. The first model estimated HRs allowing for changing deprivation fifths linked to each move and the second model fixed the deprivation fifth at the start of the study period. A third model considered deprivation change between high (the five most deprived tenths) and low deprivation (the five least deprived tenths). Results: We found 495 subjects moved between LSOAs prior to an alcohol-related death. Of these, the majority (260) moved between high deprivation LSOAs and 75 moved between low deprivation LSOAs. Slightly more subjects moved from areas of low to high deprivation (98) than the opposite (62). In model 1 subjects living in the most deprived fifth had a higher risk of alcohol-related death (HR 3.20; 95% CI 2.77 to 3.71) compared to subjects in the least deprived fifth. In model 2 the risk was little different (HR 2.96; 95% CI 2.56 to 3.42). Formal statistical adjustment for recent migration had little effect on the inequality estimates. In model 3, there was an elevated risk of alcohol-related death for moving from low to high deprivation. Conclusion: Internal migration within Wales over a six-year period does not explain the observed inequality in alcohol-related mortality.